Right illegitimate in prison: die with dignity or live without rights (Andamios, Revista de Investigación Social, 2015)
The discussion relates to the right to choose death with dignity and the prohibition imposed by law to receive help to exercise that prerogative, a matter of free choice and ethical--juridical restrictions, often frequent with respect to those involved in the suffering caused by terminal illness, but it has also been presented in the case of detainees in Mexican prisons. This circumstance results in a paradoxical dilemma created by illegitimate rules: die with dignity or live without dignity in abject humiliation?
Keywords: Prisons; rights; dignity; rules; humiliation